A resonant type AC magnetometer for evaluation of magnetic nanoparticles - Nazatul Sharreena, Suhaimi; Mohd Mawardi, Saari; Hamzah, Ahmad; Mohd Rusllim, Mohamed; Nurul Akmal, Che Lah (Springer Singapore, 2018)
Characterization of magnetic nanoparticles is crucial in order to optimize them for different applications requiring specific characteristics. In this article, we report a characterization system using AC susceptibility method. An AC magnetometer system which is composed of the induction coil and resonant capacitors is developed to evaluate the performance of the magnetic nanoparticles. The induction coil consists of excitation and detection coil. The excitation coil is designed with solenoid coils and fabricated with a Litz wire which is composed of 60 strands of copper wire with 0.1 mm diameter to reduce the increase of AC resistance at high frequency. The detection coil is designed to be a first-order differential coil which is used to reduce the environmental noise and cancel the excitation magnetic field. The detection coil is fabricated with a copper wire and it is placed at the center of the excitation coil. The excitation coil is connected to the resonant capacitors to cancel the reactant component and to permit the high magnetic field in the high-frequency region. The resonant capacitors are fabricated with multiple values of capacitors. When the developed system is in the resonant mode, the current flow is constant up to the frequency of 32.5 kHz. The developed system can evaluate the magnetic nanoparticles at different frequency responses. Using the developed system, it is shown that the Neel particles exist inside the solution of magnetic nanoparticles used in this study.